Effect of Community Education on Community Knowledge of Premature Rupture of Membranes - Aziz, Muhammad Alamsyah; Pramatirta, Akhmad Yogi; Kharismawati, Nuniek; Almira, Nadia Larastri; Sutjighassani, Tjut (Majalah Kedokteran Bandung, 2023)
Premature rupture of membranes (PROM) is still a health problem with a reasonably high incidence among pregnant women in Indonesia. The PROM is defined as the rupture of membranes before signs of labor are observed. Better knowledge on the causes, signs, symptoms, and complications of PROM is believed to help in reducing maternal and infant mortality caused by PROM. This was a cross-sectional, analytic observational study conducted in Cipacing Village, Sumedang, West Java, Indonesia during the period of June–July 2022. Community education was held to give better knowledge about PROM for women with an obstetric and gynecology specialist and fetomaternal consultant as the resource person. Total sampling was obtained from 62 women. Data were collection using pre-test and post-tests before and after the education session. The mean pre-test score was 6.48, while the mean post-test score was 7.96. A dependent T-test was used to determine the relationship between scores before and after the community education with a p-value of 0.0001. There was a significant increase in knowledge about PROM after the education session compared to before the session. This means community education is effective and impactful to increase the level of knowledge about PROM among women.